Pengembangan Media Interaktif Berbasis Contextual Teaching and Learning pada Materi Bangun Datar Kelas IV Sekolah Dasar - Syafni Gustina Sari; Rahmayuni Jusar, Ira; Wahyuni, Sri (Jurnal Pemikiran dan Pengembangan Sekolah Dasar (JP2SD), 2024)
This study aimed to develop interactive media based on Contextual Teaching and Learning (CTL) on the material two-dimensional figures for Grade V Elementary Schools. Technological developments require teachers to be more creative in developing learning media to suit the development of students who are "literate" in technology. Therefore, it is necessary to design learning media that requires students to be active and contextual in accordance with the development of elementary school students. The subjects of this study were teachers and fifth-grade elementary school students. The type of research to be carried out is research and development (R&D). The development model of this research is the 3-D (three-D) development model, namely define, design, and develop. The development consists of the validity stage, the practicality stage and the effectiveness stage. At the validity stage, CTL-based interactive media will be validated by 3 experts, namely material experts and design experts. In this paper, the development stage of the validity section will be discussed. From the definition, results obtained an analysis of learning outcomes, learning objectives, needs analysis, student analysis and concept analysis of flat shapes. At the design stage, interactive media is designed using CTL-based live worksheets. After it has been designed, it is validated by material experts and design experts. The results from material experts obtained results of 95.6 with very valid criteria, while design experts obtained results of 94.6 with very valid criteria. CTL-based interactive media is very valid and can be continued at the practicality stage